Students’ Perspective toward the Importance of English Learning for Arabic Language Education Students - Iryanti, Nurlista; Fitri Oviyanti (Global Expert: Jurnal Bahasa dan Sastra, 2024)
The 21st century is characterized as a century of openness or globalization. Life also develops over time, especially in terms of language and technological advances. English is an international language because English has become a universal language in this era. Studying English is one of the various factors to support the students in the university. Every major should have an English general class for the first semester to provide students with English basic skills. Related to the issue researchers plan to design a research entitled “Students’ Perspective toward the Importance of English Learning for Arabic Education Students”. The research aims to determine students’ perspective of what they learn related to English class and how it affects their English basic. The participants of this research were second-semester Arabic education students who had taken an English class. The participants were chosen by using purposive sampling. This research was conducted at Tarbiyah Faculty of UIN Raden Fatah located at Jalan Prof. K. H. Zainal Abidin Fikri, Palembang,  South Sumatera from December to January 2024. This research design used qualitative research. The data was collected by using a questionnaire and interview and analyzed simultaneously using Creswell’s theory about data analysis spiral to get accurate results about the issue. Keywords: English learning, Arabic student’s perspective, the importance of English